Filozófia és világnézet Tankó Béla életművében Gondolatok „Az autonóm filozofálás jegyében. Tankó Béla redivivus” című kötethez - Soltész, Péter (Gerundium, 2015)
PHILOSOPHY AND WORLDVIEW INT HE LIFEWORK OF BÉLA TANKÓ: THOUGHTS ON HIS WORK TITLED „IN TERMS OF AUTONOMOUS PHILOSOPHY: BÉLA TANKÓ REVIVED”. he work „In terms of autonomous philosophy: Béla Tankó revived” – published in 2012 and edited by László Gáspár and Tamás Valastyán – ofers an insight into the lifework of Béla Tankó (1876–1946), a Professor from Debrecen and a signiicant representative of Hungarian neo-kantianist philosophy. His work was determined by three thematic directions: (1) the theoretical consummation of philosophy, (2) its pedagogical applicability, and (3) the problem of protestantism’s social situation. hese three key issues gain equal emphasis in the work relecting the harmonic relationship of these subjects in Béla Tankó’s lifework. he essay evaluates the philosophic work of Béla Tankó and tries to situate it in the philosophic discourse of the time.